A rare and interesting case of Scarabiasis - Varghese, Sangeetha Merrin; J., Austoria A.; Koshy, Manju; Abraham, Jithin Mathew (International Journal of Contemporary Pediatrics, 2019)
Scarabiasis or Canthariasis or Beetle disease is an ectoparasitic infection of the gastrointestinal tract, in which the beetles temporarily infest the digestive tract and rarely the urinary tract. Dung beetle belongs to Scarabiaediae family. It is mostly seen in children aged between 2 to 5 years, who play outdoor for prolonged hours without undergarments. It is a temporary infestation in which early stages of development of beetle takes place in the anus and the adult beetle flies, out of the anus while defecation. A boy aged 3 years and four months presented to the pediatric OPD with complaints of peri umbilical abdominal pain, vomiting, nausea, mucus in stool along with “black insects” in his stool. The clinical examination revealed that the pulse rate, blood pressure and temperature were normal. Per rectal examination and ultrasound of the abdomen was normal. Routine examination of stool and urine was also found to be normal. The beetle was identified by the medical entomologist as dung beetle belonging to family Scarabidae. This report implies that the boy had an infestation with the larvae of dung beetle in the gastro intestine. The family belonged to the high range area of Mundakayam. Agriculture is the main source of income for people and main plantation being Rubber. Natives breed cattle for their livelihood and agriculture. During contact with mud or while playing outdoors naked, he would have come into contact with the eggs or the beetle, which hatched into larvae and caused canthariasis.